Synthesis and Evaluation of A New Series of Thiazole Derivatives as Potential Antitumor Agents and MMP Inhibitors - Asim Kaplancikli, Zafer; Dilek Altıntop, Mehlika; Atli, Ozlem; Sever, Belgin; Baysal, Merve; Edip Temel, Halide; Demirci, Fatih; Ozdemir, Ahmet (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Background: In recent years, the relationship between overexpression of matrix metalloproteinases (MMPs) and tumor invasion/metastasis has prompted researchers to develop MMP inhibitors as anticancer drugs. Objective: The aim of this study was to design and synthesize new thiazole-based anticancer agents targeting MMPs. Method: New thiazole derivatives were synthesized and investigated for their cytotoxic effects on A549 human lung adenocarcinoma, MCF-7 human breast adenocarcinoma and NIH/3T3 mouse embryonic fibroblast cell lines using MTT assay. The potential inhibitory effects of the best candidates on gelatinases (MMP-2, MMP-9), and collagenases (MMP-1, MMP-8, MMP-13) were evaluated. Results: Ethyl 2-[2-((4-amino-5-(phenoxymethyl)-4H-1,2,4-triazol-3-yl)thio)acetamido]-4-methylthiazole-5-carboxylate (3) was found to be the most promising anticancer agent against MCF-7 cell line due to its selective inhibitory effect on MCF-7 cells with an IC50 value of 20.6±0.3 μg/mL when compared with cisplatin (IC50= 35.31±0.51 μg/mL). Compound 3 also showed multiple MMP (MMP-1, MMP-8 and MMP-9) inhibitory activity (10.56±1.70, 20 and 7.28±1.49%, respectively). Conclusion: The notable anticancer activity and selectivity of compound 3 on MCF-7 cell line can be attributed to multiple MMP inhibition potential.
Keywords: anticancer activity